HOUSEHOLD ECONOMY AND HEALTH-SEEKING BEHAVIOUR IN RURAL COMMUNITIES OF AKOKO, ONDO STATE, NIGERIA (2015)
Household economy involves the production and consumption at micro level of human organisation and is characterised by cultural forces that influence actions taken to prevent and/or cure illnesses in rural communities. Existing studies on household economy in rural communities of Nigeria have focused on production and consumption patterns, without paying considerable attention to how local economic system influences health-seeking behaviour. This study, therefore examines the cultural strategies employed in household economy and their implication for choice and utilisation of healthcare services in rural Akoko communities of Ondo State. The study adopted the political economy of health theory and exploratory design. The theory posits a relationship between economic structure and health care system. One rural community was randomly selected from each of the four local government areas populated by the Akoko, namely Akoko North-west, Akoko North-East, Akoko South-West, Akoko South-East. The sampled communities are Akunnu, Ese, Ikun and Ipe-Akoko respectively. Sixteen Focus Group Discussions were conducted with men and women in the sampled households. Key Informant Interviews were conducted with purposively selected 24 health care providers, and 68 economic groups. Unstructured Observation method is also adopted for data collection. Data were subjected to content analysis. The cultural strategies adopted in household economy in rural Akoko are “Abo” (a system of organising services/labour) and “Ajugba” (a system of exchanging economic goods). Both strategies are anchored in the concept of Moye (a kinship ideology emphasising welfare creation), which demands mutual economic assistance to one’s kinsmen. However, these are principles that make household economic activities more complex and tasking in rural Akoko. The strategies affect the choice and utilisation of healthcare services. Abo encourages the flow of labour but increases time and energy expended on economic activities. It therefore limits available time to seek quality orthodox healthcare, thus, making the people to rely more on traditional healthcare and home remedies. Ajugba, on the other hand, creates availability of goods more than attracting monetary rewards to finance healthcare, and makes the people to seek cheaper healthcare. Herbal concoctions are applied for injury and pains, while home remedies are applied for curing illnesses and for preventive measures. Rural Akoko people preferred traditional healthcare and home remedies which allow them have more time for economic activities. Orthodox healthcare providers indicate that rural Akoko people devoted more attention to work than healthcare and sought orthodox healthcare at advanced stages of illnesses, resulting in morbidity and mortality. The interface between cultural strategies and the utilisation of healthcare services in rural Akoko communities indicates their importance of healthcare intervention. The cultural strategies adopted in the rural Akoko communities economic system has strong influence in determining the choice and utilisation of healthcare resources. The interface between the local economy and health-seeking behaviour in rural communities therefore deserves sustainable attention for aiding health interventions policy formulation.